Comparing the microflora of the conjunctiva and contact lens in therapeutic soft contact lens wearers - T. A. Veliksar; T. B. Gaidamaka; G. I. Drozhzhina; A. L. Molodaia; O. N. Ivanova; L. V. Dolenko; V. N. Konakh (Journal of Ophthalmology, 2020)
Background: More than 125 million (2%) people worldwide wear contact lenses (CL). Rates of CL-associated infections increase with an increase in frequency of wear of CL.